PENGARUH PENERAPAN E-COMMERCE DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN DI PT INDOLAND BATAM - Calvin, Calvin; Purba, Daris (SCIENTIA JOURNAL, 2021)
The movement in business competition, especially in the field of information technology, which is increasingly progressive and rapidly developing, can be felt by the majority of the public. The purpose of this study was to determine the existence of a positive and significant influence between e-commerce variables and service quality on customer satisfaction at PT Indoland Batam with the sampling technique using purposive sampling technique so that the number of samples in this stufy amounted to 100 respondents. Data collection method is questionnaire. Data quality test in this study uses the validity and reliability test, the classic assumption test and the influence test in this study using multiple linear regression analysis and coefficient of determination analysis (R2), while the hypothesis testing in this study uses (t test) and (F test) by using SPSS version 25 software program. From the results of the t test and F test, it can be concluded that e-commerce partially has a positive and significant effect on customer satisfaction, service quality partially has a positive and significant effect on customer satisfaction, and e -commerce and service quality simultaneously have a positive and significant effect on customer satisfaction at PT Indoland Batam.